Effect of Centella asiatica Leaf Extract on the Dietary Supplementation in Transgenic Drosophila Model of Parkinson's Disease. (26th November 2014) - Siddique, Yasir Hasan; Naz, Falaq; Jyoti, Smita; Fatima, Ambreen; Khanam, Saba; Rahul,; Ali, Fahad; Mujtaba, Syed Faiz; Faisal, Mohammad
Abstract : The role of Centella asiatica L. leaf extract was studied on the transgenic Drosophila model flies expressing normal human alpha synuclein (h- α S) in the neurons. The leaf extract was prepared in acetone and was subjected to GC-MS analysis. C. asiatica extract at final concentration of 0.25, 0.50, and 1.0  μ L/mL was mixed with the diet and the flies were allowed feeding on it for 24 days. The effect of extract was studied on the climbing ability, activity pattern, lipid peroxidation, protein carbonyl content, glutathione content, and glutathione-S-transferase activity in the brains of transgenic Drosophila . The exposure of extract to PD model flies results in a significant delay in the loss of climbing ability and activity pattern and reduced the oxidative stress (P < 0.05 ) in the brains of PD flies as compared to untreated PD flies. The results suggest that C. asiatica leaf extract is potent in reducing the PD symptoms in transgenic Drosophila model of Parkinson's disease.